Sandy soil reclamation technologies to improve crop productivity and soil health: a review - Musei, Sylus Kipngeno; Kuyah, Shem; Nyawira, Sylvia; Ng’ang’a, Stanley Karanja; Karugu, Winifred N.; Smucker, Alvin; Nkurunziza, Libère (Frontiers in Soil Science, 2024)
Sandy soils are characterized by low soil moisture content and nutrient retention due to high permeability, limiting crop productivity and threatening food security in arid and semi-arid regions worldwide. Various reclamation technologies have been developed to address these challenges, but their effectiveness has not been comprehensively evaluated. This systematic review evaluated the performance of 42 sandy soil reclamation technologies reported in 144 studies from 27 countries that met specified selection criteria. Performance was evaluated based on response ratio (RR) of aboveground biomass and grain yield, as indicators of productivity, and soil moisture content and soil organic carbon (SOC), as indicators of soil health. The 42 technologies employed four main soil amendments: biochar, organic amendments, organic amendments combined with biochar, and soft rock. Overall, all technologies increased productivity and improved soil health. Biochar application was found to be the most effective technology, increasing grain yield by 51.6%, aboveground biomass by 67.4%, soil moisture content by 17.3%, and SOC by 74.2%. Soft rock application increased grain yield by 20.3%, aboveground biomass by 27.6%, soil moisture content by 54.5%, and SOC by 12.8%. Organic amendments increased grain yield by 48.7%, aboveground biomass by 45.6%, soil moisture content by 20.8%, and SOC by 36.7%. However, the combination of biochar and organic amendments showed lower improvements, with increases of 25.4%, 15.6%, 1.3%, and 25.4% for grain yield, aboveground biomass, soil moisture content, and SOC, respectively. Our conclusion is that the findings provide strong evidence that sandy soil reclamation technologies can significantly improve crop productivity and food security. Considering the variability in technologies responses across continents, there is need for further research to determine the optimal technology for specific locations, crops, and management practices.